Feasibility and usability of experience sampling methodology for capturing everyday experiences of individuals with autism spectrum disorders - Chen, Y.; Bundy, A.; Cordier, Reinie; Einfeld, S. (Elsevier Inc, 2014)
Background: Understanding experiences from the perspective of adults with autism spectrum disorders (ASD), in the myriad of circumstances in which they find themselves every day, is crucial for developing client-centered interventions. However, capturing these experiences can be difficult. Objective: To investigate the feasibility and usability of experience sampling method (ESM), an ecological momentary assessment, for studying individuals with ASD. Methods: Four participants (2 males) with Asperger’s syndrome or high functioning autism aged 16-32 years carried an iPod touch or iPhone with a pre-installed ESM survey exploring the situation and their perceived internal experiences. Participants were asked to respond to the survey 7 times daily, at random times generated by the device, for 7 days. Results: A high signal response rate (mean=71%) and a short average time required for survey completion (mean=1 min 42 s) supported feasibility of the ESM for use in research with individuals with ASD. Participants reported that the questions were straightforward and that survey completion interfered very little with everyday activities, supporting acceptability of the method. Results of a split week analysis revealed consistency of experiences; correlations among experiences that are linked logically provided evidence of the internal logic of data gathered using the ESM. Through graphic analysis, we illustrated the usability of ESM for capturing the influence of everyday contexts on internal experiences/perceptions. Conclusions: The ESM holds promise for examining the impact of social context on the everyday experiences of individuals with ASD.